Rancang Bangun Alat Perajang Singkong Dengan Pisau Horizontal Menggunakan Pendorong Pegas - Pebriansyah Pebriansyah; Saparin Saparin; Eka Sari Wijianti; Rodiawan Rodiawan; Yudi Setiawan (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
Cassava (Manihot esculenta Crantz), also known as tapioca or cassava, is one of the main tuber crops cultivated in humid tropical regions. In addition to being a staple food source, cassava is also used to produce tapioca flour and cassava chips through a shredding process. Cassava shredding can be done manually with traditional tools or made easier by using technology in the form of a shredding machine. However, the use of shredding machines still faces obstacles such as relatively long time and uneven shredded results. This machine is designed to increase the quantity and quality of shredded results. Horizontal knives and spring-shaped pushers are used in the machine. The way this machine works is by rotating the blade using a 125 watt electric motor, using 2 blades and machine dimensions of 60 cm long x 30 cm wide x 40 cm high. The results of this study were carried out 3 times, obtaining an average yield of 886 grams and an average time of 80.41 seconds with a production capacity of 40.636 kg / hour and a production efficiency of 88.6%.